Usos e apropriações das praças públicas em cidades médias: reflexões sobre Feira de Santana - Carneiro, Leidiane Evangelista Alves (2022)
Debates about public spaces are relevant both in the academic context and in the scope of planning and management, since they allow us to identify and understand the configuration of the city. The present work was based on the study of public squares in Feira de Santana, having as its object the Praça do Cruzeirinho, Petrolínio Pinto Cunha and Santa Monica squares, which enabled the investigation of how they are being used and the factors that contributed to their use and/or disuse. In this context, it aimed to analyze the forms of uses and appropriations of public squares in medium-sized cities by different social groups, as well as the environment and the processes that contribute to strengthen the use in the search for understanding the relationship (or not) of the population with these spaces. The research used as methodological means the bibliographic and documental surveys; direct observations, in which photographic records were taken; semi-structured interviews with representatives of the Green Areas Maintenance Department, and with young, adult, elderly and disabled residents who live near the study locus; and an opinion poll, through a survey that was made available on social networks. The research found that the above- mentioned squares, despite the concerns of the residents about the lack of public action to promote improvements and acts of violence, are used by the population. Also, that there is resistance, because despite the dissatisfactions, the squares are options for use and spaces for struggles and cultural expressions.